2017
DOI: 10.22489/cinc.2017.148-302
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Heart Rate Variability Measures During the Oral Glucose Tolerance Test

Abstract: Heart rate variability (HRV) exhibits a different response to different external stimuli (emotional, auditory, etc). In this paper, HRV irregularity and correlations in short time scales were assessed after a sudden increase in plasma glucose concentration (a stimulus of glucose), using approximate entropy (ApEn) and short-term fluctuation (α1) of detrended fluctuation analysis, respectively, in people with metabolic syndrome and healthy control subjects. 5-min RR interval time series were extracted from ECG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Although the study was limited to just 1 person, it corroborated the results achieved by Fujimoto et al [ 28 ] where that ratio was first identified to be negatively correlated with blood glucose concentration. In 2017, Perpiñan et al [ 29 ] assessed the impact of taking a 75 g oral glucose testing in 25 subjects, 15 with metabolic syndrome, and 10 as a control group. They identified that the metabolic syndrome subjects presented significant higher HRV irregularity than the control group after 30 min of glucose intake.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the study was limited to just 1 person, it corroborated the results achieved by Fujimoto et al [ 28 ] where that ratio was first identified to be negatively correlated with blood glucose concentration. In 2017, Perpiñan et al [ 29 ] assessed the impact of taking a 75 g oral glucose testing in 25 subjects, 15 with metabolic syndrome, and 10 as a control group. They identified that the metabolic syndrome subjects presented significant higher HRV irregularity than the control group after 30 min of glucose intake.…”
Section: Literature Reviewmentioning
confidence: 99%